DIGITIZATION AND DOCUMENTATION OF TANGALIYA CRAFT: A STUDY OF ITS DESIGN PRACTICES IN SURENDRANAGAR, GUJARAT - Saiyed, Shohrat; Bhatia, Reena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tangaliya, a 700-year-old handloom textile weaving tradition upheld by the Dangasia community of Surendranagar represents a vibrant cultural heritage of Gujarat. The textile intricately woven and adorned with unique dana, created through warp binding technique. This technique is visible only in Tangaliya textile craft. This textile serves as lower garments for the women of the Bharwad community. It is traditionally woven on a hand-operated throw shuttle pit loom. Due to the limited width of the loom, it is woven in two halves and after weaving two continuous half lengths, it is separated and hand-stitched from the center. “Desi Oon” i.e. regional sheep wool is used as raw material which was historically provided by the Bharwad (the user community). Tangaliya were traditionally woven in the villages of Surendranagar district, Gujarat. The study focused on covering the design process followed by the weavers and converting the traditional motifs into Computer-Aided Design (CAD). The data was collected through field visits through interviews and observation. The understanding of design development from the weavers' perspective was gained and documented. The layouts of traditional tangaliya layouts were prepared in CAD and explored in different colourways.